The Missing Colors of the Rainbow: Black Queer Resistance - Elena Kiesling (European Journal of American Studies)
This paper traces the historical context of queer activism and black activism from the social movements of the 1960s and 1970s in the U.S. in order to show the deep rift between blackness and queerness that comes into full force in a supposedly colorblind nation that more than once claimed that “gay is the new black.” This is not only a dangerous analogy that lacks profound grounding, it also leads to a discourse that draws a clear boundary between two separate communities and movements—one black, one queer. Recent activism by #BlackLivesMatter has challenged the analogy of blackness and queerness by centralizing both in their critique of state-sanctioned violence against black people. The analysis of Nneka Onourah’s documentary The Same Difference provides further insight into the complex array of power that affect the lived experiences at the intersection of queerness, blackness, and gender. The documentary generates points of departure through which queerness finds validity as a tool for critical thinking, a way of active resistance, and a basis for community action. Placing the documentary in context, this article reconstructs a paradigm for radical queer politics in the force-field of traditional notions of black masculinity and femininity and queerness as a destabilizer of both, bringing queerness back into a marginal position from which it can be critical of the state.